Analisis Pengaruh Kualitas Layanan, Kepuasan, dan Loyalitas terhadap Niat Berperilaku Pasien Rumah Sakit Umum Daerah (RSUD) Jayapura - Ruben Tuhumena; Surachman -; Eka Afnan Troena; Margono Setiawan (Jurnal Aplikasi Manajemen, 2011)
Unit sample at this research is inpatients on General Hospital Regional (RSUD) Jayapura. The respondents of the research are 300 persons (patients) are taken using purposive sampling method, while the 4 (four) informants are taken using purposive sampling method. Structural Equation Modeling (SEM) with program assistance of Analysis Moment Structures (AMOS) is used analyze the quantitative data, while the qualitative data uses interactive model. The results of this research show that: (1) inpatient services is judged as service with sufficient quality. (2) The patient felt quite satisfied with hospital services. (3) The patient showed sufficient loyalty attitude towards the hospital. (4) Patients indicatedquite favorable behavior intention (5) improved quality of services can improve patient satisfaction and loyalty, but not the patients’behavior intention. (6) Increased patient satisfaction may improve patient loyalty and patients’ behavior intention in line with the increasing of patient loyalty. (7) Iincreased in customer loyalty can increase the patient behavior intention. (8) The model used in this study showed that the biggest contribution is the influence of service quality toward satisfaction, then satisfaction toward loyalty, and loyalty toward the patient behavior intention.Keywords: Service quality, Satisfaction, Loyalty, Behavior Intention